Eksplorasi Etnomatematika pada Seni Batik Madura dalam Pembelajaran Geometri - Tri Ardilia Maya Sari; Alkaromah Nur Sholehatun; Syifa Aulia Rahma; Rizky Budi Prasetyo (Pendidikan Matematika STKIP Kusuma Negara, 2021)
Batik is an extraordinary work of art that must be preserved, it can be through formal or non-formal education. So far, cultural products are not always recognized for their usefulness in the scope of formal education. This study aims to map mathematical concepts on Madura batik that can be integrated in mathematics learning. This research is a qualitative descriptive study with an ethnographic approach by conducting observations and interviews, then a literature study is carried out related to the geometry. The instrument in this study is a human instrument, the researcher is directly related to the research and acts as a data collector. The data were analyzed by making codes which were then reduced based on the concepts and learning materials of geometry. The results of this study in the form of mathematical concepts contained in the Madura Batik motif are: straight line, curved line, parallel line, symmetry, point, angle, triangle, circle, rhombus and similarity concept. Some Madura batik motifs can be used as a medium to introduce mathematical concepts such as concepts in geometry so that it is expected to make it easier to understand abstract mathematical concepts.